Clinical Characteristics of Cutaneous Melanoma and Second Primary Malignancies in a Dutch Hospital-Based Cohort of Cutaneous Melanoma Patients. (6th December 2009) - van der Velden, Haike M. J.; van Rossum, Michelle M.; Blokx, Willeke A. M.; Boezeman, Jan B. M.; Gerritsen, Marie-Jeanne P.
Abstract : The increasing number of living cutaneous melanoma patients and the increased risk of developing a second primary tumour incited us to analyse the clinical characteristics of cutaneous melanoma and define the frequency, site, and type of second primary cancers in cutaneous melanoma patients. We collected data on patients who visited the Department of Dermatology at the Radboud University Nijmegen Medical Centre and were newly diagnosed with cutaneous melanoma or metastasis of melanoma with unknown primary localization between 2002 and 2006. A total of 194 cases were included; eleven patients developed a subsequent melanoma, 24 had at least one basal cell carcinoma, three had at least one squamous cell carcinoma, and 21 patients had a second non-cutaneous primary malignancy. In conclusion, 48 patients developed a subsequent malignancy. As nonmelanoma skin cancer is the most frequent second malignancy, our results subscribe to the necessity of follow-up by a dermatologist.